Strategic sequential voting - Julio González-Díaz; Florian Herold; Diego Domínguez (Bamberg University, Bamberg Economic Research Group (BERG), 2016)
In this paper, we study the potential implications of a novel yet natural voting system: strategic sequential voting. Each voter has one vote and can choose when to cast his vote. After each voting period, the current count of votes is publicized enabling subsequent voters to use this information. Given the complexity of the general model, in this paper we study a simplified two-period setting. We find that, in elections involving three or more candidates, voters with a strong preference for one particular candidate have a strategic incentive to vote in an early period to signal that candidate's viability. Voters who are more interested in preventing a particular candidate from winning have an incentive to vote in a later period, when they will be better able to tell which other candidate will most likely beat the one they dislike. Strategic sequential voting may therefore result in voters coordinating their choices, mitigating the problem of a Condorcet loser winning an election due to mis-coordination. Furthermore, a (relatively) strong intensity of preferences for the preferred candidate can be partially expressed by voting early, possibly swaying the choice of remaining voters.
Keywords: D72; D71; C72; 330; sequential voting; elections; endogenous timing; strategic timing